Total Arsenic Concentrations in Sea Turtle Tissues from the Mediterranean Coast of Spain - Martínez-López, E.; Herrero, D.; López-Berenguer, G.; Peñalver, J. (Bulletin of environmental contamination and toxicology, 2021)
In this work we studied total arsenic concentrations in liver, muscle and kidney of 49 individuals of two sea turtle species (loggerhead sea turtles, n = 45; leatherback turtles, n = 4) stranded in Murcia (South-eastern Spain) coastline between 2009 and 2018. In accordance with the literature, muscle was the tissue with the highest concentrations in both species, followed by liver and kidney. Although differences in arsenic concentrations were not statistically significant between the study species, loggerhead sea turtles showed concentrations two or three times higher than those of leatherback turtles, which we attribute to differences on feeding behavior and habitat preferences. Arsenic concentrations in turtles from this area increase evidence of western Mediterranean Sea as a hotspot for metal pollution. Based on the scarce existing knowledge on arsenic toxicity in sea turtles, those levels found in our study are below those responsible for liver damage.